Penelitian Konseling Islam: Analisis Isi 37 Tahun - Rifqi Muhammad; Patriana Patriana; Yusrain Yusrain; Manja Manja; Enik Sartika; Astaman Astaman (Kuras Institute, 2022)
Researchers conducted a content analysis for 37 years of Islamic counseling research consisting of 23 articles in Scopus indexed journals. The purpose of this study is to describe the evaluation of Islamic counseling research from 1985-2022. This study uses content analysis. The study was coded into eight content categories, namely: 1) marriage, 2) education, 3) occupation/career, 4) social, 5) religious, 6) development of models, techniques, Islamic counseling instruments, 7) utilization of concepts from Islamic teachings, Islamic leaders, Islamic culture, 8) Counselee problems, 9) Interventions and stages/processes of Islamic counseling, 10) Utilization of technology in Islamic counseling. In addition to coding the 23 articles into content categories, the researcher also classified the research methodologies; qualitative, quantitative, or mixed methods and R&D. The results show that 2021 is the highest number of articles for 37 years of Islamic counseling research in Indonesia with four articles written by Indonesian researchers; the research design of the researcher found that the conceptual analysis of Islamic counseling dominated the 23 articles as much as 47% or 11 conceptual articles. Furthermore, it is dominated by qualitative research as much as 35% or 8 articles. Then the articles came from quantitative research as much as 9% or only 2 articles. Furthermore, mix and research and development each 1 article or 5%; of the 8 categories of content analysis, only the field of work does not have articles; In the rankings, Noor Shakirah Mat Akhir is the biggest contributor, followed by Norazlina Zakaria, Abdurrahman and Saiful Akhyar Lubis in the third position; The Islamic Guidance and Counseling Journal appears to be the largest publisher of Islamic counseling articles starting in 2020 and 2021. The findings of this study provide direction for future research that needs to examine the search results of the google scholar indexer publish or perish from 1985 to 2022 with keywords Islamic counseling is 1,000 articles.